Optimalisasi Pengelolaan Sampah melalui Sosialisasi Zero Waste dan Implementasi Pipa Biopori dalam Program Kerja KKN Desa Kuranji, Lombok Barat - Qolbuna Salima, Baiq; Rizqi Pramana, Adhimas; Munandar, Aris; Ziadha Naufal Firdaus, Baiq; Gede Windu Sukma Govinda, I; Anasta Irawan, Islam; Kadek Minarti, Ni; Setiawati, Kadriani; Khaerunnisa; Munawarah, Zahratul; Buhari, Nurliah (Universitas Mataram, 2025)
Kuliah Kerja Nyata (KKN) Kuranji Village, West Lombok, focuses on waste management through Zero Waste socialization and the implementation of biopore infiltration pipes. The Zero Waste concept is applied based on the 3R principles (Reduce, Reuse, Recycle) to minimize waste accumulation. One of the methods used is biopore, which consists of infiltration holes that facilitate the decomposition of organic waste while enhancing water absorption. The program begins with public socialization involving the local government, followed by the construction of biopore holes using PVC pipes. Organic waste, such as food scraps and leaves, is placed into the biopore pipes to accelerate decomposition. Regular maintenance is carried out by adding rice washing water to support microbial activity. As a result, the community has demonstrated an increased understanding of waste management, while the biopore pipes have proven effective in reducing waste buildup and improving soil quality. This program highlights the importance of active community participation in achieving sustainable waste management. Consequently, Kuranji Village is expected to serve as a model for implementing the Zero Waste concept and promoting more environmentally friendly waste management practices.